Social media as political hatred mode in Malaysia’s 2018 General Election - Chinnasamy Sara; Abdul Manaf Norain (SHS Web of Conferences, 2018)
In the era of technological advancement, with smartphones and digital devices, almost everybody can have access to the Internet. We move at very fast pace along with the information that we carry and every each of it will rapidly processed. Especially on social media platforms, where false news or scandals that revolve around pundits or the higher up often create chaos and triggers public interest. Malaysia had its 14th General Election (GE14) dated 9th May, 2018. It was believed to be the most nerve-wracking, fiercest general election to ever happen where after 61 years, Barisan Nasional (BN) had to bow down to the voice of Malaysians where social media is part of the factor, utilised ultimately to influence the people and powerful enough to change people’s perception, thus, create political hatred. A textual analysis was conducted on 187 news on six online news stations’ social media platform during the 11 days of campaigning. In-depth interviews were also conducted to discover the political hatred issues on social media. The findings suggested issues like Goods and Service Tax (GST), candidates’ reputations and 1 Malaysia Development Berhad (1MDB) scandal are the main causes of political hatred expressed on social media platforms.